Reliability of Measurements on Plaster and Digital Models of Patients with a Cleft Lip and Palate - R. Burcu Nur Yılmaz; Derya Germeç Çakan; Merve Altay; Halil ibrahim Canter (Galenos Yayinevi, 2019)
Objective:The purpose of this study was to determine (1) the more and less reliable measurements/methods and (2) the influence of knowledge and skill on the inter- examiner, intra-examiner, and inter-method reliability of nasolabial measurements on plaster casts and three dimensional (3D) stereophotogrammetric images of casts in infants with an unrepaired unilateral cleft lip and palate (UUCLP).Methods:Preoperative extraoral plaster casts from 42 patients with UUCLP were measured with a digital caliper, and the image acquisition of casts was performed with the 3dMDface stereophotogrammetry system (3dMD, Atlanta, GA). Two examiners (one postgraduate student, one lecturer) evaluated 19 nasolabial measurements in two separate sessions.Results:Intra-rater, inter-rater, and inter-method reliability was lower in measurements of nasal, philtral, and nasal floor width. Almost all of the interclass correlation coefficients (ICC) for measurements performed by the lecturer were above 0.75, whereas the intra-examiner reliability of some measurements performed by the postgraduate student showed low ICC (<0.75).Conclusion:Measurements of curving slopes, such as nasal width, of small dimensions, such as nostril floor width, and deformity-affected anatomic parts, such as philtrum width, presented a low reliability. Measurements on 3D images showed a higher reliability compared to plaster model measurements performed by the postgraduate student. Therefore, it may be recommended to use 3D digital images of infants with CLP for nasolabial measurements especially if performed in postgraduate settings.